Assessment of Nutritional Knowledge, Dietary Habits and Nutrient Intake of University Student Athletes - Ali, Amanat; Al-Siyabi, Muhammad S.; Waly, Mostafa I.; Kilani, Hashem A. (Pakistan Journal of Nutrition, 2015)
Despite the importance of physical activity and training, the optimum nutrient intake and good nutritional knowledge have been recognized as important factors in improving the athletic performance and health status of athletes. The present study was conducted to assess the nutritional knowledge, dietary habits, nutrient intake and nutritional status of Sultan Qaboos University student athletes. A cross-sectional study design was used to achieve the objectives. Seventy one (49 male and 22 female) student athletes with a mean age of 21.0±1.81 and 19.32±0.72 years and body mass index (BMI) of 22.51±1.98 and 20.34±2.97 kg/m2 for male and female respectively, participated in study. All subjects were interviewed in person. The study questionnaire consisted of questions related to demographic information, nutritional knowledge and a 7-days food diary to identify nutrient intake, food frequency and variety of food consumption. Significant differences (p